Evaluation of phytochemical and nutritional potential of Talinum triangulare (Jacq) leaf, stem and root on human health - Ilodibia, Chinyere; Igboabuchi, Ngozi (International Journal of Biological Research, 2016)
Phytochemical and nutritional potentials of various parts (leaf, stem and root) of Talinum triangulare were evaluated using standard techniques. Analysis of Variance (ANOVA) was employed in data analysis. All the parts of the species were found to contain nutrient compositions in varying levels. Dry matter and carbohydrate were highest in the stem (91.69±0.12 and 68.66±0.01) respectively. Moisture, ash content and crude fibre were highest in the root (9.78±0.04, 17.53±0.11and 15.32±0.03) respectively while ether extract and crude protein were highest in the leaf (1.09±0.01 and 17.72±0.17) respectively. The results showed also varying quantities of the phytochemicals in the leaf, stem and root with some parts lacking some of the phytochemicals. The leaf contained the highest percentage of all the phytochemical investigated alkaloid, flavonoid, tannin, sterol, Terpenoid, phenol and saponin (0.47±0.01, 0.26±0.00, 0.36±0.07, 0.03±0.01, 0.42±0.02, 0.02±0.01and 0.68±0.05 respectively. The root lacked sterol and phenol while stem lacked only phenol. The leaf, stem and root lacked cyanogenic glycoside. The results have indicated that these parts of the Talinum triangulare investigated are very nutritious and possessed bioactive compounds that could be extracted for the manufacture of new drug, food supplements and also be used in ethnomedicine for the treatment of diseases.